Training in Europe - Wiji Arulampalam; Alison L. Booth; Mark L. Bryan (Institute for the Study of Labor (IZA), 2003)
Using the European Community Household Panel, we investigate gender differences in training participation over the period 1994-1999. We focus on ?lifelong learning?, fixed-term contracts, part-time versus full-time work, public/private sector affiliation, educational attainment, and the individual?s position in the wage distribution prior to training. Women are typically no less likely than men to train. While there is no significant training-age profile for women, there is a negative profile for men. In several countries there is a negative association between fixed-term contacts and training, particularly for men. In most countries and, for both sexes, training is positively associated with public sector employment, high educational attainment and a high position in the wage distribution.
Keywords: J40; J24; J16; 330; work-related training; gender; fixed term contracts; Weiterbildung; Berufsbildung; Geschlecht; Lebenslanges Lernen; Befristeter Arbeitsvertrag; Schätzung; EU-Staaten